The functionally elusive RabI chromosome configuration directly regulates nuclear membrane remodeling at mitotic onset. Issue 15 (3rd August 2017) - Fernández-Álvarez, Alfonso; Cooper, Julia Promisel
ABSTRACT: Despite its ubiquity in interphase eukaryotic nuclei, the functional significance of the RabI configuration, in which interphase centromeres are clustered at the nuclear envelope (NE) near the centrosome and telomeres localize at the opposite end of the nucleus, has remained mysterious. In a broad variety of organisms, including Schizosaccharomyces pombe, the RabI configuration is maintained throughout mitotic interphase. The fission yeastli nker ofn ucleoskeleton andc ytoskeleton (LINC) complex mediates this centromere association. The functional significance of centromere positioning during interphase has been recently revealed using a conditionally inactivated LINC allele that maintains LINC stability but releases interphase centromere-LINC contacts. Remarkably, this interphase release abolishes mitotic spindle formation. Here, we confirm these observations using an alternative strategy to explore the role of centromere-NE association without modifying the LINC complex. We analyze spindle dynamics in cells lacking Csi1, a stabilizer of centromere-LINC associations, and Lem2, a NE protein harboring lamin interacting domains. We recapitulate these observations and their implications for the functional significance of centromere positioning for cell cycle progression in fission yeast and most likely, a wide range of eukaryotes.